Reversibly Photo‐Modulating Mechanical Stiffness and Toughness of Bioengineered Protein Fibers. Issue 6 (9th December 2020) - Sun, Jing; Ma, Chao; Maity, Sourav; Wang, Fan; Zhou, Yu; Portale, Giuseppe; Göstl, Robert; Roos, Wouter H.; Zhang, Hongjie; Liu, Kai; Herrmann, Andreas
Abstract: Light‐responsive materials have been extensively studied due to the attractive possibility of manipulating their properties with high spatiotemporal control in a non‐invasive fashion. This stimulated the development of a series of photo‐deformable smart devices. However, it remained a challenge to reversibly modulate the stiffness and toughness of bulk materials. Here, we present bioengineered protein fibers and their optomechanical manipulation by employing electrostatic interactions between supercharged polypeptides (SUPs) and an azobenzene (Azo)‐based surfactant. Photo‐isomerization of the Azo moiety from the E ‐ to Z ‐form reversibly triggered the modulation of tensile strength, stiffness, and toughness of the bulk protein fiber. Specifically, the photo‐induced rearrangement into the Z ‐form of Azo possibly strengthened cation–π interactions within the fiber material, resulting in an around twofold increase in the fiber's mechanical performance. The outstanding mechanical and responsive properties open a path towards the development of SUP‐Azo fibers as smart stimuli‐responsive mechano‐biomaterials. Abstract : Bioengineered protein fibers were prepared through electrostatic complexation of a positively charged polypeptide and a negatively charged azobenzene‐based surfactant. The photo‐isomerization of the azobenzene moiety from E ‐ to Z ‐isomer reversibly triggered a modulation of the bulk protein fiber's mechanical performance.